Incidentally Found Rectal Carcinoid Tumor in a 46-Year-Old Female: The Potential for Complications and the Importance of Screening Guidelines - Lapides, Rebecca; Shah, Akash; Bal, Shubhneet; Ramapriya, Vidhun (International Journal of Medical Students, 2023)
BACKGROUND: Carcinoid tumors are rare neuroendocrine tumors that can be found in the gastrointestinal tract as well as other areas throughout the body. The neurosecretory nature of these tumors can have implications for other chronic diseases that patients may have, including diabetes and hypertension. Certain treatments that may be implemented for patients that have carcinoid tumors, such as somatostatin analogs and Everolimus, can also alter blood glucose control. This highlights the importance of diagnosing and treating carcinoid tumors as early as possible to avoid complications associated with metastasis and more intense treatment. With more advanced disease, clinicians should consider the possible effects of carcinoid tumors and their treatments on other chronic conditions as they manage the patient. For gastrointestinal carcinoid tumors, colonoscopy screening guidelines are incredibly important to counsel patients on, as resection can yield a complete cure for carcinoid tumors when they are found at an early stage. THE CASE: We describe the case of an incidentally diagnosed rectal carcinoid tumor in a 46-year-old female patient with a history of type 2 diabetes mellitus and hypertension. This tumor was discovered on colonoscopy, which had been delayed due to complications following a surgical procedure that the patient had recently undergone. CONCLUSION: Carcinoid tumors are quite rare, however, the incidence of neuroendocrine tumors, including gastrointestinal carcinoid tumors, is growing. Thus, it is important to consider the implications of such tumors on pre-existing chronic conditions, such as diabetes and hypertension. Also, more research efforts should be directed towards standardizing the treatment protocol for such tumors, specifically rectal carcinoid tumors, and counseling patients on the importance of screening guidelines. When rectal carcinoid tumors are caught early, complete surgical resection can be curative, which is ideal. However, with more advanced disease, symptoms of the tumor itself as well as necessary treatments can impact other chronic conditions, possibly requiring modifications to a patient’s prior medication regimen. Fortunately, the carcinoid tumor in the described patient was not advanced enough to cause significant alteration in her other chronic conditions, however, this case is still a great example of how carcinoid tumors can arise asymptomatically, which is why it is important for the astute clinician to counsel on screening recommendations. This emphasizes the importance of using a team-based approach to ensure that the carcinoid tumor is diagnosed and adequately treated without significantly affecting other conditions so that patients can achieve optimal outcomes for each condition being managed. It also highlights the crucial importance of screening guidelines so that conditions can be caught early to mitigate downstream consequences.